COVID-19 Vaccine Uptake, Acceptance, and Reason for Vaccine Hesitancy: A Cross-Sectional Study Among Pregnant Women in Trinidad, West Indies [Letter] - Tampake R; Mangundap SA; Saman (Dove Medical Press, 2023)
Rina Tampake,* Selvi A Mangundap,* Saman* Department of Nursing, Poltekkes Kemenkes Palu, Palu, Indonesia*These authors contributed equally to this workCorrespondence: Selvi A Mangundap, Faculty of Nursing, Poltekkes Kemenkes Palu, Thalua Konchi Street Number 09, North Palu, Palu, Center Sulawesi, Indonesia, Email selvi.541.am@gmail.com